The Current Status of the Polish Language in Ivano-Frankivsk (Formerly Stanislaviv) - Olena Pelekhata (Cognitive Studies | Études cognitives, 2020)
The Current Status of the Polish Language in Ivano-Frankivsk (Formerly Stanislaviv)